LANDSLIDES OF THE ARMENIAN HIGHLAND (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
In the paper the types and causes of landslides of the Armenian highland is analysed. Their highest activity is observed in the provinces of Trabzon, Rize, Erzurum and Shirnak (all in Turkey); in the Adjaristskali river head and in the Bordjomi gorge of Kura River (Georgia); in the provinces Vayots Dzor, Ararat and Tavush (Armenia). The most of them are coincided with zones of active faults and hydrothermal changed rocks and the active use of mountain slopes increases the risks of their displacement.
Keywords: Armenian highland; landslides; faults; seismic activity